A maturity model for assessing sustainable project management knowledge areas: A case study within a logistics firm - Elifcan Göçmen (Journal of Advanced Research in Natural and Applied Sciences)
Currently, the use of maturity models is widespread for evaluating the success of project management (PM) processes. Project management maturity models (PMMM) are valuable methodologies to improve the project management processes. In this context, this present paper seeks an answer to these questions: Which maturity levels are aimed for an organization to make the sustainable PM sound? Which propositions are made based on the obtained maturity levels? This paper aims to propose a PMMM by analysing PM knowledge areas. In response to this objective, nine dimensions and twenty seven maturity items are handled using of PM Solutions’ PMMM. In order to evaluate the maturity levels, Weighted Maturity Score Calculation Model (WMSC) approach based on survey questionnaires of two experts is used first for the PM knowledge areas. Weighted average score of all maturity items is obtained using Likert-scale and criteria weights are first calculated using Hesitant Fuzzy Analytical Hierarchy Process (HF-AHP). Practicality of these approaches is illustrated through a real data in a logistics organization. As a result, computational results indicate that risk management dimension with the level 1,4 has the lowest rating of all nine dimensions. The high maturity level 3,5 is observed in the quality management, as the maturity items in this dimension such as Quality Plan Preparation and Quality Plan Employment can have a favourable impact on the PM maturity. The findings reveal the effectiveness of the proposed method, which ensures practical and theoretical insights for organizations to determine their current and expected sustainable project maturity levels.